Parliamentary crisis follows Turkish elections: Constitutional and Kurdish questions demand resolution yet opposition refuses cooperation - Günter Seufert (Stiftung Wissenschaft und Politik (SWP), 2011)
In the weeks leading up to the Turkish parliamentary elections on 12 June, there was much talk of potential danger in the Turkish and Anglo-American media. Prime Minister Recep Tayyip Erdoğan, it was claimed, was set to impose a dictatorship of the conservative majority, so people should vote for the opposition. Without a strong counterweight to guarantee the participation of all political currents in the drafting of a new constitution, there was a threat of the emergence of a presidential system tailored to Erdoğan himself. As it turns out, the scenario of authoritarian majority rule was overblown and instead Turkey's real problems come to the fore again. The judiciary continues to be instrumentalised for political ends, and there is a lack of an opposition to hold the government to deeper democratisation by espousing credible liberal positions. But the biggest headache is the Kurdish problem, which is coming to a head again
Keywords: 320